Citra Kabupaten Tanah Datar Sebagai Destinasi Wisata: Persepsi Wisatawan Dan Dampak Ekonomi Pariwisata - Fajri; Elvina Primayesa (Jurnal Ragam Pengabdian, 2026)
This article is developed from a thesis on the image of Tanah Datar Regency as a tourist destination based on tourist perceptions. It aims to analyze the factors shaping destination image, explain the economic impact of tourism through Marginal Propensity to Consume (MPC) and economic multiplier, and formulate policy implications for regional tourism development. The study applies a mixed-methods approach using primary data from 200 tourists visiting major destinations and tourism events in Tanah Datar Regency. Quantitative analysis includes validity and reliability tests, Kaiser-Meyer-Olkin (KMO), Bartlett’s Test, Exploratory Factor Analysis (EFA), Principal Component Analysis (PCA), and MPC-multiplier calculations. The findings show that Tanah Datar’s destination image is a multidimensional construct shaped by leisure and tourist amenities, shopping and culinary experience, local residents and social environment, political stability, adventure and climate, local culture, cleanliness and environmental quality, and personal safety and convenience. The local MPC is 0.2515, generating an economic multiplier of 1.336, while economic leakage reaches 74.85%. These results indicate that tourism contributes to the local economy, but local income circulation remains suboptimal. Strengthening destination image should be integrated with local MSME development, local products, digital promotion, amenity quality, safety, cleanliness, and community-based tourism to enhance the sustainable economic impact of tourism.